The synthesis and characterisation of some ortho-substituted phenoxyalkanoic acids and their derivatives - VALENTIN BADEA; IOANA IENASCU; CORNELIU TARABASANU; IULIANA POPESCU; ALFA XENIA LUPEA (Journal of the Serbian Chemical Society, 2006)
The synthesis of 2-phenoxyalkanoic acids (ethanoic, propanoic, butanoic) was realised by the reaction of ortho-hydroxybenzamide respectively N-phenyl-o-hydroxybenzamide with a-halogenated acids in aqueous sodium hydroxide solution. 2-[o-(carbamoyl)phenoxy]-2-methyl- and 2-[o-(phenylcarbamoyl)phenoxy]-2-methyl- propanoic acids were obtained by reaction of the appropriate amide with acetone, chloroform and sodium hydroxide. Ethyl esters of 2-phenoxyalkanoic acids were obtained by the reaction of the amide with ethyl esters of a-halogenated acids in different reaction media. Starting from the ethyl esters of 2-[2-(N-phenylcarbamoyl) phenoxy]alkanoic acids with hydrazine 2-[2-(N-phenylcarbamoyl)phenoxy]alkanoic acids hydrazides were obtained, which are considered key intermediates for the synthesis of several series of new compounds. Schiff bases and N-imido-derivatives were obtained by condensation of hydrazide with substituted aromatic aldehydes respectively maleic anhydride. The synthesized compounds were characterized by physico-chemical methods (FTIR, NMR and mass spectrometry).